Introduction of means of electronic study in the system of the higher education - Маракушин Андрій Ігоревич (Andriy Marakushyn); Чередніченко Артем Вікторович (Artem Cherednichenko) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to estimate results of introduction of means of "electronic study" at physical training of students of Simon Kuznets Kharkiv national university of economics. Material and methods: the research was conducted during 2013/14 in KhNUE among students of the first and second courses. In general for about 800 students took part in the research. Results: the system of the remote study (SRS) Chamilo is characterized; the algorithm of introduction of SRS Chamilo in physical training of students is developed, applied and analysed; the analysis of the empirical data obtained as a result of the research is carried out. Conclusions: it is proved that SRS Chamilo is a platform which completely meets the demands which are made to the modern software, and can be used in physical training of students. The algorithm of its introduction to the noted sphere is logical and complete; it is established that there is an actual question of studying of motives of students of rather regular classes of physical training and sport, and also uses of means of "electronic study"; conclusions of scientists are confirmed that "electronic" communication can’t replace "alive" one, and can be only its addition.